Behavioral differences in early detection of cervical cancer through self-assessment using KarS-A (Aim scorecard) - Nadhiroh, A’im Matun; Winarti, Eko; Saudah, Noer; Ramadhani, Firdausi (BKM Public Health and Community Medicine, 2024)
Purpose: To find cases of cervical cancer as early as possible by using self-assessment through KarS-A (Aim Score Card). Methods: The research design used a quasi-experimental approach with a pre-post test control group design. The number of samples at this stage was 230 WUS. The treatment group in the Sepulu subdistrict consisted of 115 WUS, while the control group in the Burneh subdistrict consisted of 115 WUS. The variables studied were self-assessment and WUS behavior. The statistical tests employed in the third stage are the chi-square test and logistic regression. Results: This research showed differences in the behavior of WUS with self-assessment and WUS without self-assessment, with a P value <0.05. In the behavioral variable, a p-value of 0.010 was obtained, which meant that there was an influence between self-assessment and the positive behavior of women of childbearing age for early detection of cervical cancer, with an OR of 7.200. Women who had conducted self-assessments and received a high-risk score had up to 7.2 times the chance of carrying out early detection compared to women who received a low-risk score, with a 95% CI value of 1.595-32.504. Conclusion: Self-assessment affects WUS behavior. Women with a high-risk score were 7.2 times more likely to undergo early detection as compared to women who got low scores.